tq - cos"2"x tq "2"x=
упростить выражение
31 декабря 2012 - Администратор
Рейтинг: 0
Голосов: 0
468 просмотров
Комментарии (0)
Нет комментариев. Ваш будет первым!
tq - cos"2"x tq "2"x=
упростить выражение
tq - cos"2"x tq "2"x=
упростить выражение
Решение: tg x- cos (2x) tg (2x) =tg x- ((1-tg^2 x)\(1+tg^2 x))*2tg x\(1-tg^2 x)=
=tg x-2*tgx\(1-tg^2 x)=tg x(1-2\(1-tg^2 x))=
=tg x(1-tg^2 x-2)\(1-tg^2 x)=-tg x *(1+tg x)\((1+tg x)*(1-tg x))=
-tg x\(1-tg x)=tg x\(tg x -1))
Ответ: tg x\(tg x -1))
Источник: https://znanija.com/task/245453
Нет комментариев. Ваш будет первым!